Euro Area Policies : Financial Sector Assessment Program-Technical Note-Stress Testing the Banking Sector. (IMF Staff Country Reports; Country Report ;, 2018)
The FSAP team undertook a thorough top-down stress testing analysis using end-2017 data. This note covers the methodology and results of the scenario-based solvency tests, the single factor sensitivity tests, and the liquidity tests. The stress test exercise was carried out on a sample of major euro area banks supervised by the Single Supervisory Mechanism (SSM). The analysis is heavily dependent on comprehensive and granular supervisory data on individual banks' positions shared by the European Central Bank (ECB). While FSAP results are not directly comparable to the 2018 EU-wide stress test results due to differences in scenarios, methodologies, and objectives, they provide an assessment of the system-wide resilience of the euro area banking sector at the current juncture.